PENGARUH SOCIAL LEISURE ACTIVITY TERHADAP PENURUNAN RISIKO WANDERING PADA LANSIA DEMENSIA DI RSJ Dr. RADJIMAN WEDIODININGRAT LAWANG MALANG: The Effect of Social Leisure Activity for Decreased Risk of Wandering on Dementia Elderly in Mental Health Hospital Dr. Radjiman Wediodiningrat Lawang Malang - Amalia - Kusumaningsih; Ahmad Yusuf; AV Sri Suhardiningsih (Jurnal Ilmiah Keperawatan (Scientific Journal of Nursing), 2020)
Introduction: Dementia is a clinical syndrome of decline in cognitive function. Dementia with various neuropsychiatric symptoms can have a large impact on both clients and caregivers, one of which is wandering behavior. Wandering is a neuropsychiatric symptom that is difficult to control, challenging, at risk of loss, causes various risks of fracture, and even death. Wandering management still uses traditional methods until now. The purpose of this study was to determine the effect of Social Leisure Activity in reducing the risk of wandering. Methods: The design of this study was quasi-experimental with a pre-post test one group. The study population was 47 elderly and a sample of 34 elderly dementia along with their caregivers who were outpatients at the Psychogeriatric Clinic of Dr. RSJ Radjiman Wediodiningrat Lawang. The sampling technique used purposive sampling method. The independent variable in this study was the Social Leisure Activity and the dependent variable was wandering risk. The instrument used Elopement Screening to assess the risk of wandering, the KATZ Independence Index, and the Caregiver Training questionnaire. The intervention was carried out at home by the caregiver in the form of a series of activities carried out for 4 weeks with a frequency of 3 times a week and 45 minutes per activity. The caregiver was given training as well as a demonstration of wandering and social leisure activity before the research was conducted. Data were analyzed using Paired-Samples T-Test. Results: The results of the analysis showed that there were significant differences (p = 0,000) on the value of the risk of wandering before and after an intervention. Training data on the caregiver gave a result that there was a significant difference (p = 0,000) in the caregiver's knowledge before and after training. Discussion: The risk of wandering in dementia elderly could be reduced by providing regular physical activities that prioritize elements of social interaction. Social Leisure Activity is an effective activity to be developed because it is easy to implement and efficient because it does not require high costs. Conclusions and Suggestions: Social Leisure Activities can help reduce the risk of wandering if done regularly and continuously. Social Leisure Activity can be used as an alternative for caregivers and elderly dementia to keep on doing activities.